Alternative investments in precious metals - Siemaszkiewicz, Karolina (Inwestycje alternatywne w metale szlachetne, 2019)
The alternative investments industry has become an important part of the global economy and financial system, in which one can consider hedge funds, precious metals and other commodities or art investments. This paper analyses the potential benefits from adding precious metals (gold, silver, platinum) and also copper to portfolio investments from the perspective of investors from the Czech Republic, Hungary, Poland, and Slovakia, compared to those of German Stock Exchange. The PX, BUX, WIG, SAX and DAX indices were used to represent the market. The analyses cover the period 2007-2018 to compare the different performance of stock exchange indices at that time. The authors compare diversified portfolios using the Sharpe, Treynor and Jensen coefficients and beta coefficient. The beta coefficient, in most considered periods, of precious metals is at a low positive or even negative level. This may show that precious metals can be considered as alternative investments. However, one has to remember that each of these metals is characterized by different investment characteristics such as return rate of risk and volatility
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 12, s. 125-137